Dental implants in medically compromised patients undergoing or after receiving anti-resorptive or radiotherapy: retrospective clinical and radiographic data - Mertens, Christian; Staudinger, Fabian; Smielowski, Maximilian; Rückschloß, Thomas; Schnug, Gregor; Hoffmann, Jürgen; Ristow, Oliver (Clinical oral implants research, 2025)
Objective and Aim A retrospective study to evaluate the clinical and radiological outcomes of dental implants placed in compromised patients who have undergone antiresorptive therapy (AR) or head and neck radiotherapy (IR). Material and Methods Dental implant placement was evaluated in compromised patients undergoing or after receiving AR/IR therapy following specific preventive measures: antibiotic prophylaxis (2 days before and 5 days after surgery) and primary wound closure with submerged healing for 4 months. The primary outcome was implant survival during the observation period. Secondary outcomes included marginal bone loss, occurrence of osteonecrosis, and factors influencing implant survival. Results A total of 92 patients (59 IR, 32 AR) with 369 dental implants were included in the study. During a mean follow-up period of 25 months (SD: 16), 23 implants were lost (IR: 21, AR: 2). Implant survival rates were 92% and 98% for IR and AR, respectively. Identified risk factors for implant failure included placement in neomandibular/−maxillary sites, maxillary implantation, implant diameter < 4.2 mm, active smoking, and diabetes mellitus. The mean marginal bone loss was 0.57 mm (SD: 1.51) in the IR group and −0.09 mm (SD: 1.17) in the AR group. Conclusion With comprehensive risk assessment and careful evaluation of implant indications, dental implants can serve as an effective dental rehabilitation option for patients undergoing or after receiving AR/IR therapy, provided strict adherence to preventive measures is maintained. Implants placed following AR therapy demonstrate higher survival rates and reduced marginal bone loss compared to those placed after IR therapy.
Gesehen am 14.01.2026